Analysis of the Application Restorative Justice Principles in the Settlement of Land Disputes that Occurred in Merauke Regency South Papua Province - Parera, Zegovia; Suradinata, Poetri Enindah (Faculty of Law, Musamus University, 2024)
From a legal perspective, this study examines the extent to which existing regulations, both at the national and local levels, support and accommodate the application of restorative justice in the context of land disputes. The analysis will include an in-depth study of Law Number 11 of 2012 concerning the State Administrative Court, Government Regulation Number 24 of 1997 concerning Land Registration, and relevant regional regulations. In addition, this study will also identify legal obstacles that hinder the application of restorative justice. The research method used is a qualitative method with a case study approach. Data collection was carried out through in-depth interviews with the disputing parties, community leaders, customary leaders, and law enforcement officers. In addition, this study will also analyze relevant legal documents and regulations. The results of this study are expected to contribute to the development of a more comprehensive understanding of the application of the principle of restorative justice in the context of overlapping land disputes in Merauke. The findings of this study are also expected to be the basis for the preparation of more effective policy recommendations in resolving land disputes in the future, while still respecting the rights of indigenous peoples and the principles of restorative justice.